Light Spectrum Impacts on Growth, Molting, and Oxidative Stress Response of the Mud Crab Scylla paramamosain - Chen, Shujian; Shi, Ce; Migaud, Herve; Song, Changbin; Mu, Changkao; Ye, Yangfang; Wang, Chunlin; Ren, Zhiming (Frontiers in Marine Science, 2022)
An 8 weeks trial was performed to test the effects of light spectra [full-spectrum, violet (405 nm), blue (470 nm), cyan (500 nm), green (525 nm), yellow (570 nm), and red (625 nm)] on growth performance, molting, antioxidant capacity, stress response and expression of molting, and apoptosis-related genes in Scylla paramamosain. Results showed that spectrum had a significant effect on S. paramamosain physiology. Compared to blue light, crabs exposed to violet light had a significantly lower survival rate (79.5 ± 3.6% vs. 94.9 ± 3.6%), weight gain (49.2 ± 5.4 vs. 67.6 ± 6.7), molt frequency (4.2 ± 0.2 vs. 4.5 ± 0.1), and extended intermolt intervals between instar 1 and 2 stages (C1–C2) (6.3 ± 0.3 vs. 5.0 ± 0.1 days). Expression of the molt-inhibiting hormone (mih) gene was upregulated in crabs reared under violet light. According to the regression analysis, maximum SGR would be at 449.97 nm. Crabs exposed to blue light also had lower melatonin levels than under full-spectrum and lower cortisol levels than violet and yellow groups. Regarding oxidative stress, crabs in full-spectrum had lower H2O2 and MDA contents, however, no significant difference was found in total antioxidant capacity (T-AOC), superoxide dismutase (SOD), and catalase (CAT) in hepatopancreas from crabs under different spectra. Gene expression of hsp40, hsp70, hsp90 were down-regulated in crabs exposed to the full-spectrum light group. Regarding apoptosis-related genes, bcl-2 gene expression in crabs under cyan and the cox IV and caspase 3 in green were upregulated, suggesting cyan light may inhibit, while green light may promote apoptosis. Taken together, these results suggest that blue or cyan light would promote growth performance, while full-spectrum light could reduce stress response in S. paramamosain.